Peningkatan Kemampuan Mahasiswa Dalam Mata Kuliah Praktikum Dasar Elektrik Melalui Model Pembelajaran Inkuiri - Suartini, Tuti (INVOTEC, 2010)
This study aims to determine the ability and attitude of students in solving problems after the applicationof learning models inkuiri on paraktikum courses. Research method used is Classroom Action Reasearch (CAR) isdone in three cycles. Each cycle consists of four stages, namely planning, action, observation, and reflection. Fromthe research results obtained that the model implemented in the learning lab inkuiri electric base, in general anincrease in the learning process and results of each cycle. Cognitive test results through the pre test and post test onthe cycle I in terms of percentage of students who reach the value of 0% 6 is increased to 94.875%, in cycle IIincreased from 6.25% to 93.375%, and the third cycle of 3.125% increase to 100%. The results of the task undertakenby the students increased each cycle. Then for the activity sheets teachers viewed from the observation activitycategory shows an increase of the cycle is the cycle I and II into either category III cycle. For student activity showsmost categories of cycle I and cycle II rose to the category in general the third cycle. Impressions and attitudes ofstudents through filling the questionnaire stated that by applying the learning model inkuiri conditions become moreactive class, students become able to appear in her opinions.